2015
DOI: 10.2166/wqrjc.2015.051
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cu(II) on natural and treated clays

Abstract: We have studied the pH and the temperature effects on copper ions' adsorption on natural and treated clays from Algeria. The clay was also treated to improve the adsorption capacity. X-ray diffraction identified montmorillonite and kaolinite as major clay minerals. The Langmuir adsorption model was used for the mathematical description of the adsorption equilibrium and the equilibrium data adhered very well to this model. The treated and natural clay had a monolayer adsorption capacity equal to 15.40 and 12.22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, treated Algeria clay under similar condition as the untreated clay has adsorption capacity of 15.40 mg/g [105]. The process of adsorption was spontaneous and exothermic [105]. Sorption of copper (II) ion on palygorskite and sepiolite is enhanced at elevated temperature [106].…”
Section: Mixture Of Oxide Clay And/or Other Materialsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, treated Algeria clay under similar condition as the untreated clay has adsorption capacity of 15.40 mg/g [105]. The process of adsorption was spontaneous and exothermic [105]. Sorption of copper (II) ion on palygorskite and sepiolite is enhanced at elevated temperature [106].…”
Section: Mixture Of Oxide Clay And/or Other Materialsmentioning
confidence: 97%
“…Another study found that low-cost adsorbent Algeria clay that is composed of predominantly montmorillonite and kaolinite has the capacity of adsorbing Cu(II) at pH of 6.5 and 20°C with maximum adsorption capacity of 12.22 mg/g [105]. However, treated Algeria clay under similar condition as the untreated clay has adsorption capacity of 15.40 mg/g [105]. The process of adsorption was spontaneous and exothermic [105].…”
Section: Mixture Of Oxide Clay And/or Other Materialsmentioning
confidence: 99%
See 1 more Smart Citation